Purchase Decision pada Marketplace dengan Purchase Intention sebagai Mediator - Fauzi, Erika Gustian; Kesumahati, Erilia (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
Focus of this research is to see how brand image, social media marketing, easiness, price and e-service quality affect the purchase decision of goods in the marketplace mediated by purchase intention in Batam City. SmartPLS application is used to test the data of respondents. The purposive sampling method was used for non-probability sampling. The main data was collected through a questionnaire distributed with Google Form via WhatsApp and social media. The result of this research that brand image has a significant effect on purchase decision, social media marketing has a significant positive effect on purchase decision, easiness has a significant positive effect on purchase decision, price has a significant positive effect on purchase decision, and e-service quality has no significant effect on purchase decision. Brand image has a significant positive effect on purchase intention, e-service quality has a significant positive effect on purchase intention. The indirect effect of brand image, easiness and e-service quality has a significant positive effect on purchase decision through purchase intention. The object model and other variables are expected to be developed and expanded for further research.